Effects of in vitro polyploidization on agronomic characteristics and fruit carotenoid content; implications for banana genetic improvement - Amah, D.; Biljon, A. van; Maziya-Dixon, B.B.; Labuschagne, Maryke T.; Swennen, Rony L. (Frontiers Media, 2019)
Bananas (Musa spp.), native to South East Asia, have spread worldwide and are integrated into the diets of millions of people in tropical regions. Carotenoid content varies dramatically between different banana genotypes, providing an opportunity for vitamin A biofortification. Polyploidization is a useful tool for crop improvement with potential to generate new diversity, especially in a polyploid crop like bananas. Ten induced tetraploids generated from six diploid banana genotypes were evaluated for their agronomic attributes and fruit carotenoid content in comparison to their diploid progenitors. Tetraploids had distinct plant morphology, but generally displayed inferior vegetative and yield characteristics with 20% lower bunch weights than their original diploids. Similarly, a 50% decrease in fruit provitamin A carotenoids (α-carotene, 13-cis β-carotene, 9-cis β-carotene, trans-β-carotene) accompanied by a corresponding increase in lutein was recorded in induced tetraploids in comparison to their original diploids. Additionally, all lines were subjected to pollen viability tests to assess their fertility. Pollen viability tests indicated over 70% viability for induced tetraploids and diploid controls, suggesting their possible use in crosses. These findings provide a basis for the application of induced polyploidization in bananas to generate useful genetic material for integration in hybridization programmes aiming to produce vitamin A enriched triploids valuable to malnourished populations.